Uruguay : Report on the Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2014)
This Report on the Observance of Standards and Codes-Data Module provides an assessment of Uruguay's macroeconomic statistics against the Special Data Dissemination Standard (SDDS), complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework 2012. The findings suggest that Uruguay exceeds the SDDS timeliness requirements for labor market (employment, unemployment, and wages/earnings), price (consumer prices and producer prices), and international investment position data. Currently, Uruguay is using two regular timeliness flexibility options for general government operations and central government operations. In addition, it is using an 'as relevant' timeliness provision for analytical accounts of the banking sector for countries with extensive branch banking systems. No flexibility options are being used regarding real sector statistics.